Case report: An asymptomatic mother with an inborn error of cobalamin metabolism (cblC) detected through high homocysteine levels during prenatal diagnosis - Liu, Yu-Peng; He, Ru-Xuan; Chen, Zhe-Hui; Kang, Lu-Lu; Song, Jin-Qing; Liu, Yi; Shi, Chun-Yan; Chen, Jun-Ya; Dong, Hui; Zhang, Yao; Li, Meng-Qiu; Jin, Ying; et al. (Frontiers in Nutrition, 2023)
Background The most common disorder of the intracellular cobalamin metabolism pathway is the combined methylmalonic acidemia and homocysteinemia, cblC type (cblC). There is a variation in its clinical spectrum ranging from severe neonatal-onset forms that are highly fatal to later-onset forms which are milder. In this study, the first case of an asymptomatic Chinese woman with a defect in congenital cobalamin (cblC type) metabolism at prenatal diagnosis due to elevated homocysteine level is identified. Case presentation The proband, a male child born to a 29-year-old G1P0 mother, admitted to local hospital with feeding disorder, intellectual disability, seizures, microcephaly, as well as heterophthalmos. The level of the urine methylmalonic was elevated. Equally found were increased blood propionylcarnitine (C3) and propionylcarnitine/free carnitine ratio (C3/C0) and decreased methionine levels. The plasma total homocysteine level was elevated at 101.04 μmol/L (normal < 15 μmol/L). The clinical diagnosis of combined methylmalonic acidemia and homocysteinemia was supported. Four years later, the mother of the boy married again and came to us for prenatal diagnosis exactly 15 weeks after her last menstrual period. Subsequently, there is an increase in the amniotic fluid methylmalonate. The level of the amniotic fluid total homocysteine was marginally high. A considerably elevated amniotic fluid C3 was equally observed. In addition, there is a respective significant increase in the plasma and urine total homocysteine at 31.96 and 39.35 μmol/L. After the sequencing of MMACHC genes, it is found that the boy, a proband carried a homozygous mutation of the MMACHC at c.658_660delAAG. While the boy's mother, she carries two mutations in MMACHC: c.658_660delAAG and c.617G>A. The fetus is a carrier of the MMACHC gene. Following the administration of routine treatment, the mother remained symptom-free in the course of pregnancy, and she gave birth to a healthy boy. Conclusion Variable and nonspecific symptoms characterized the cblC type of methylmalonic acidemia combined with homocysteinemia. Both biochemical assays and mutation analysis are recommended as crucial complementary techniques.